The Theory of the Knowledge Square: The Fuzzy Rational Foundations of the Knowledge-Production Systems - Dompere, Kofi Kissi (Studies in Fuzziness and Soft Computing, 2013)
The monograph is about a meta-theory of knowledge-production process and the logical pathway that connects the epistemic possibility to the epistemic reality. It examines the general conditions of paradigms for information processing and isolates the classical and fuzzy paradigms for comparative analysis. The book is written for professionals, researchers  and students working in philosophy of science, decision-choice theories, economies, sciences, computer science, engineering and related subjects. It is further aimed at research institutions and libraries. The subject matter belongs to extensive research and development taking place on fuzzy phenomena and the debate between the fuzzy paradigm and the classical paradigm relative to informatics, synergetic science and complexity theory. The book will have a global appeal and across disciplines. Its strength, besides the contents, is the special effort that is undertaken to make it relevant and accessible to different areas of sciences and knowledge production.